Conservation agriculture as a climate change mitigation strategy in Zimbabwe. Issue 3 (3rd May 2020) - O'Dell, Deb; Eash, Neal S.; Hicks, Bruce B.; Oetting, Joel N.; Sauer, Thomas J.; Lambert, Dayton M.; Thierfelder, Christian; Muoni, Tarirai; Logan, Joanne; Zahn, James A.; Goddard, John J.
ABSTRACT: There is a need to quantify agriculture's potential to sequester carbon (C) to inform global approaches aimed at mitigating climate change effects. Many factors including climate, crop, soil management practices, and soil type can influence the contribution of agriculture to the global carbon cycle. The objective of this study was to investigate the C sequestration potential of conservation agriculture (CA) (defined by minimal soil disturbance, maintaining permanent soil cover, and crop rotations). This study used micrometeorological methods to measure carbon dioxide (CO2 ) flux from several alternative CA practices in Harare, central Zimbabwe. Micrometeorological methods can detect differences in total CO2 emissions of agricultural management practices; our results show that CA practices produce less CO2 emissions. Over three years of measurement, the mean and standard error (SE) of CO2 emissions for the plot with the most consistent CA practices was 0.564 ± 0.0122 g CO2 m −2 h −1, significantly less than 0.928 ± 0.00859 g CO2 m −2 h −1 for the conventional tillage practice. Overall CA practices of no-till with the use of cover crops produced fewer CO2 emissions than conventional tillage and fallow.